Integrated Vehicle Health Management: Essential Reading - Jennions, Ian (SAE International, 2013)
Brings together a collection of twenty-two SAE International Technical papers organised according to specific areas of interest: Engines, Airframes, Electrical Power Systems, Supporting Systems, and Architecture.